2018
DOI: 10.1080/13102818.2018.1532318
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of bioactive ingredients of Salvia miltiorrhiza and advanced biotechnologies for their production

Abstract: This review deals with the progress in the biosynthesis and regulation of tanshinones and salvianolic acids as well as the prospects and challenges for producing such compounds through biotechnology techniques. Tanshinones (lipophilic diterpenoids) and salvianolic acids (hydrophilic phenolic acids) are valuable natural products from danshen (Salvia miltiorrhiza Bunge) with remarkable clinical efficacy to treat cardiovascular diseases, with potential application in the treatment of cancer and possibly other dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The other compound, SA-B, was also found in the root and the potent therapeutic effects which are mainly for cardiovascular diseases [4]. It has been reported that tanshinones are synthesized via the terpenoid pathway, whereas salvianolic acids through the phenylpropanoid pathway [24]. In this study, the root extract of 4 x plants accumulated significantly higher concentration of DT-I than 2 x plants.…”
Section: Discussionmentioning
confidence: 62%
“…The other compound, SA-B, was also found in the root and the potent therapeutic effects which are mainly for cardiovascular diseases [4]. It has been reported that tanshinones are synthesized via the terpenoid pathway, whereas salvianolic acids through the phenylpropanoid pathway [24]. In this study, the root extract of 4 x plants accumulated significantly higher concentration of DT-I than 2 x plants.…”
Section: Discussionmentioning
confidence: 62%
“…Salvia miltiorrhiza Bunge (Lamiaceae, Salvia), also known as Danshen, has demonstrated notable antioxidant, antibacterial, anticoagulant, and anti-tumor activities and has been commonly used to treat cardiovascular diseases for almost 2,000 years [ 15 17 ]. As a mycorrhizal-dependent medicinal plant, S. miltiorrhiza can form a good symbiosis with various AMFs [ 18 – 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…19−21 Phenylalanine ammonia-lyase (PAL), cinnamic acid 4-hydroxylase (C4H), 4-hydroxycinnamic acid CoA-ligase (4CL), tyrosine aminotransferase (TAT), hydroxyphenylpyruvate reductase (HPPR), rosmarinic acid synthase (RAS), and cytochrome P450-dependent monooxygenase (CYP98A14) were involved in RA biosynthesis. 19,20,22 However, the direct evidence for the formation of SAB from RA is still absent in the literature. natural products and serves as an alternative to extraction from plant biomass.…”
Section: ■ Introductionmentioning
confidence: 99%
“…From the view of the chemical structure, SAB can be seen as the condensation product of two molecules of caffeic acid (CA) and two molecules of 3,4-dihydroxyphenyllactic acid (DHPL, also named danshensu or salvianic acid A) or the coupling product of two RA phenoxyl radicals (Figure ), and laccase was assumed to be responsible for the formation of SAB from RA in S. miltiorrhiza. , In plants, RA is proposed to be synthesized through the condensation of 4-coumaroyl-CoA and 4-hydroxyphenyllactic acid, followed by 3- and 3′-hydroxylation, or the coupling of 4-coumaroyl-CoA and DHPL, followed by 3-hydroxylation, starting from phenylalanine and tyrosine. Phenylalanine ammonia-lyase (PAL), cinnamic acid 4-hydroxylase (C4H), 4-hydroxycinnamic acid CoA-ligase (4CL), tyrosine aminotransferase (TAT), hydroxyphenylpyruvate reductase (HPPR), rosmarinic acid synthase (RAS), and cytochrome P450-dependent monooxygenase (CYP98A14) were involved in RA biosynthesis. ,, However, the direct evidence for the formation of SAB from RA is still absent in the literature.…”
Section: Introductionmentioning
confidence: 99%